Change in texture improvement of low‐fat tofu by means of low‐fat soymilk protein denaturation. (15th July 2014) - Shin, Woo‐kyoung; Yokoyama, Wallace H; Kim, Wook; Wicker, Louise; Kim, Yookyung
Abstract BACKGROUND Tofu made from low‐fat soy flour is a nutritional food for consumers and economically benefits the food processor. However, low‐fat tofu has poor textural quality, especially insufficient firmness. Stepwise heating (heating at 75 °C, followed by holding at 95 °C) of full‐fat soymilk increases gel properties. Therefore we evaluated the two‐step heating of low‐fat soymilk to improve tofu texture. RESULTS The denaturation enthalpy and temperature of β‐conglycinin and glycinin were higher in low‐fat tofu compared to high‐fat tofu. The viscosity of low‐fat soymilk and texture of tofu by one‐step heating were weaker than full‐fat soymilk and tofu. However, the two‐step heating increased free sulfhydryl groups and viscosity of low‐fat soymilk to a value higher or similar to conventional soymilk. The syneresis of low‐fat tofu was reduced about 30% and hardness was higher (131.0 N) by the two‐step process compared to one‐step heating of full‐fat tofu (101.4 N) by the one‐step process. The microstructure of low‐fat tofu became finer, denser and more homogeneous by the two‐step heat process. CONCLUSION Low‐fat tofu produced by denaturing the two major soy proteins separately had improved textural qualities similar to full‐fat tofu as a result of increased hydrophobic interactions between denatured protein molecules. © 2014 Society of Chemical Industry